Sugarcane bagasse hydrolysate as a potential feedstock for red pigment production by Monascus ruber - Terán Hilares R. (2018)
This work was supported by the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica CONCyTEC-Perú (Grant number 219-2014) and Conselho Nacional de Desenvolvimento Científico e Tecnológico CNPq-Brazil, (Grant number 449609/2014-6 and 168930/2017-0). Authors are grateful to Fundação Oswaldo Cruz (Fiocruz) –Brazil by the donation of microorganism.